Sosialisasi Pencegahan Kekerasan dan Perundungan (Bullying) di SMP Islam An-Nadhliyah Mambaul Ulum Sangatta Selatan Kabupaten Kutai Timur - Mutasyarifin, Aham; Fauzi, Moh. Ibnu Faruk; Jarya, Haenul; Wahyuningsih, Sulistia; Priyambada, Muhammad Nabil (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
Bullying remains a recurring form of violence in school environments and has significant negative impacts on students’ psychological well-being, social development, and academic performance. This community service program (PkM) aimed to enhance students’ understanding of the types of Bullying, its consequences, and preventive measures through an educational socialization activity conducted at SMPI An-Nadhliyah Mambaul Ulum, Sangatta Selatan. The program employed direct counseling, expert-led material presentations, and interactive discussions. A total of 40 students, including class representatives and members of the OSIS (Student Council), participated in the activity. The results indicate that students responded positively to the program and demonstrated improved ability to identify various forms of Bullying that were previously unfamiliar to them. Based on verbal feedback and observation, the activity effectively increased students’ awareness of the importance of creating a safe, respectful, and violence-free school environment. The school management also expressed its commitment to strengthening preventive efforts through continuous supervision and guidance for students. Overall, this program proved effective in improving anti-bullying literacy and reinforcing a supportive and safe school culture.